Effectiveness of Al-Qur'an Tadabbur Therapy on Nulliparous Women’s Anxiety Level during Labor - Nurul Auliya Kamila; Rosa Mutianingsih (Global Medical & Health Communication, 2021)
The process of pregnancy affects psychological aspects significantly. This process may lead to anxiety and inconveniences. The previous research showed that anxiety might be contributing to the labor process. These can decreased baby birth weight and increased hypothalamic-pituitary-adrenal (HPA) hormone levels which cause changes in steroid hormone production and adult fertility rates. Besides, anxiety during pregnancy impacts emotional problems, disorders of hyperactivity, decentralization, and impaired child development. Nonpharmacological therapy that has been approved in reducing anxiety is religious copings. One of the religious copings is to contemplate (tadabbur) Al-Qur'an. Al-Qur'an can treat all kinds of diseases, including anxiety disorders. This study aims to examine the effect of Al-Qur'an tadabbur therapy on reducing nulliparous anxiety levels during labor. A quasi-experimental study was conducted with a pretest-postest control group design. The sampling technique was consecutive sampling. The number of 30 third trimester nulliparous women experienced moderate-severe anxiety levels in Tanjung Karang Public Health Center, Mataram was selected to participate in this study during July–September 2020. They were divided into two groups, the intervention and control groups. The intervention group received Al-Qur'an tadabbur therapy, while the control group was not. The statistical analysis used was univariate and bivariate analyses with an independent t test. The instrument was used as the Zung Self-Rating Anxiety Scale (SAS) questionnaire. This study showed that the decrease of anxiety score in the intervention group was 26.1% higher than the control group p=0.001 (p<0.05). In conclusion, Al-Qur'an tadabbur therapy is effective in reducing anxiety levels during labor.